2017
DOI: 10.4172/2476-2261.1000112
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Transfusion Refractoriness among Patients with Hematological Malignancies in a Tertiary Center in Saudi Arabia

Abstract: Patients with hematological malignancies (HMs) and that undergoing hematopoietic stem cell transplantation (HSCT) for HMs or other disorders require multiple blood product transfusions. Approximately 30% of these patients develop platelet transfusion refractoriness (PTR), which increases the risk of serious and potentially fatal bleeding complications. The incidence of PTR in the Saudi population is unknown.To determine the occurrence of PTR in adult HMs and HSCT patients at King Abdul-Aziz Medical City (KAMC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…An observational study with reduced leukocyte blood components showed that 44% of platelet transfusions failed to produce a satisfactory response (Stanworth et al, 2015). A study at King Abdul-Aziz Medical City, Riyadh, reported that platelet refractory occurred in 16.7% of patients with hematological malignancies who underwent platelet transfusion (Abuelgasim et al, 2017). It is estimated about two-thirds of refractory platelets are non-immune, and another 20% is a combination of immune and non-immune.…”
Section: Introductionmentioning
confidence: 99%
“…An observational study with reduced leukocyte blood components showed that 44% of platelet transfusions failed to produce a satisfactory response (Stanworth et al, 2015). A study at King Abdul-Aziz Medical City, Riyadh, reported that platelet refractory occurred in 16.7% of patients with hematological malignancies who underwent platelet transfusion (Abuelgasim et al, 2017). It is estimated about two-thirds of refractory platelets are non-immune, and another 20% is a combination of immune and non-immune.…”
Section: Introductionmentioning
confidence: 99%